Democratic support and corruption: Lessons from East Europe - Dominik Enste; Martin Acht (Institut der deutschen Wirtschaft (IW), 2018)
It has been recognized that the support for democracy seems to be increasing with the time spent in a democratic system. An individual's life experience living under democratic rule positively affects the support for democracy as a political system. Therefore it seemed inevitable that the newly democratic eastern European member countries of the European Union would reap the benefits of democratization and slowly foster democratic support. However, recent backlashes to democratic rule in those countries seem to be contradictory. Therefore this paper investigates whether people's rising democratic capital in these new democracies also increases the support for democracy in those countries. Furthermore we examine if the quality of other institutions and especially corruption play a role in shaping the support for democracy and whether the positive effect of democratic capital on democratic support might be undermined. We find that the recent repercussions to democratic rule in eastern European countries are no coincidence. The effect of people's rising democratic capital on the support for democracy is negative in those countries. It has therefore been falling. Moreover, we establish that the increased experiences of corruption in these states undermine the support for democracy. Specifically, that democracy and corruption are complementary institutions. Only in the absence of corruption can the experience of democracy have its full effect on prodemocratic attitudes.
Keywords: D02; D72; P37; 330